If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 3 + -5x = 0 Reorder the terms: 3 + 11x + -5x = 0 Combine like terms: 11x + -5x = 6x 3 + 6x = 0 Solving 3 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 0 + -3 6x = 0 + -3 Combine like terms: 0 + -3 = -3 6x = -3 Divide each side by '6'. x = -0.5 Simplifying x = -0.5
| -x(13+4x)=-3(5-9x)+2 | | (7x+2)+(18-7x)= | | r^3+4r^2=0 | | -115+x=9x+93 | | 5(2-x)+10x-8=27 | | x^2-10x=e^2 | | (6+5)8=N+40 | | 6(4x+6)+3x= | | 2(x)-3=5 | | y=x^2-4+2 | | (16x-7)+(12-2x)= | | 3ln(8x)=24 | | (6x+15)+10= | | x^3-7x^2+8x=0 | | 11x-16=12x+9 | | 6(5x+5)+6x= | | h-(h*h)=0.18 | | 11(3x+9)-12x= | | 0=3x^2-12x+10 | | 2(w+1)+w=7-4w | | 0.06-0.01(x-1)=-0.02(2-x) | | -3x-37=47-7x | | 9(3x+9)-5= | | 7/3x-1=2x | | y=5/2x-1(5,3) | | 15.27=.965*x-.548 | | 2/1-3x-3=-4 | | 6X-4Yndy=4x+2 | | 7x^2-24x+104=0 | | 12y-3[y+5]=48 | | 3(4x+12)+7x-15= | | 2sin^2x+5sinx=1 |